Adaptação do Indicador de Salubridade Ambiental (ISA) para análise do saneamento básico na cidade de Brejo Grande/SE - Santos, Fernanda Flores Silva dos (2016)
In Brazil, to serve the population with total sanitation services is still a challenge. Despite of the visible progress indicators that show the expansion of the sanitation sector in Brazil pointed to by the last census of the IBGE (2010), the shares still performed insufficiently reached the real needs of the population. Public policies aimed at achieving the universality of this sector in the country, thus obtain positive impacts on public health and is necessary to have preventive actions involving the health of the environment. In the municipality of Brejo Grande deficiencies in sanitation combined with the cultural habits conducted by the population in water bodies, such as washing clothes, bathing and farming, and the very economic conditions of the same, certainly exposes to health disorders. To achieve satisfactory levels through health becomes key measure levels of environmental indicators in a certain locality. Thus, this study aimed to analyze the sanitation conditions in the seat of the municipality of Brejo Grande/SE and its influence on public health, through the adaptation of the Environmental Health Indicator (ISA). The adaptation was necessary because the research focus is based on the analysis of sanitation in the study area, as well as the need to obtain information to assess the health status of the population. The ISA was called to this work as ISA/BG, as it is specific to this location. Their analysis took place from the Sub-water supply indicator, Sub-Solid Waste Indicator, Sub-Sewage indicator, Sub-Drainage indicator Urban and Sub-Public Health Indicator. For this study, a descriptive exploratory and qualitative and quantitative nature was developed. The data used to feed the ISA/BG and interpret the results were collected in the field with the community and government agencies of federal, state and municipal levels. From the results it was found that the existing sanitation infrastructure in urban Brejo Grande, negatively interfere with the health of the population. And that despite the actions taken and in progress by the municipality of Brejo Grande, carried out in order to fulfill determined by the National Sanitation Policy, the difficulties they pass the sanitation sector in the country, are reflected in the locality of study.